The Moral Education as a Public Affair - Bonifacio Barba Casillas (Universidad Autónoma de Madrid, 2018)
This article presents an approach to the comprehension of the moral education in Mexico as well as its political analysis. Considering that the Mexican society is living a transition process in which the social and economic expectations on the education have relevant changes, a review of the national projects of education throughout two centuries of the independent Mexico is done, placing them in the context of the liberal thought and on the formation of the Mexican state.  With this perspective, the text has the intention to promote a comprehension of the moral education as a public matter of great importance in the formation of individuals as citizens. It offers a future view in which it is fundamental to understand the moral education as a complex activity and as an essential condition for the accomplishment of the liberal reason in the integration of the social action, the governmental action and the school action.